Dosimetric comparison and clinical correlation between conventional four field radiotherapy versus three-dimensional conformal radiotherapy in cancer cervix - Shubhi Agarwal; Dr. Arvind Kumar Chauhan; Piyush Kumar; Jitendra Nigam; Pavan Kumar (International Journal of Medical Research and Review, 2019)
Introduction: With sectional imaging, wide variations are reported in pelvic anatomy of individual patients raising concerns over adequate coverage of target volume with conventional radiotherapy based on standard bony landmarks. Three-dimensional conformal radiotherapy (3DCRT) is reported to decrease normal tissue toxicity, along with decrease in chances of geographic miss. Present study is done for dosimetric comparison of Planning Target Volume (PTV) and Organs at Risk (OAR) in cancer cervix patients treated with conventional and conformal radiotherapy along with clinical correlation in terms of side effects and tumor response.Materials and Methods: Fifty patients of cancer cervix underwent planning contrast enhanced CT scan. Target volumes & OAR were contoured. Patients were randomized into conventional & conformal arms. Conventional fields were planned using standard bony landmarks. CT based radiotherapy planning was done for 3DCRT arm. Field sizes &dose volume histogram (DVH) were recorded & compared for target coverage & OAR sparing in both arms. All patients received concurrent chemotherapy followed by brachytherapy.Results: Field sizes used for the 3DCRT plans were significantly larger than those used for the conventional plans (p= 0.000). Optimal PTV coverage was significantly improved using 3DCRT as compared to conventional radiotherapy (p= 0.0001). Dose homogeneity in both arms were almost similar (p= 0.292), while conformity index was better in 3DCRT which was statistically significant between the groups (p= 0.000). Mean dose to the Planning Target Volume was increased significantly in the CT based plan when compared with the standard four field plan (p= 0.0001).Difference in doses to the organs at risk (urinary bladder, and small bowel)and their side effects were statistically significant across both groups. There was no difference in tumor response.Conclusion: The present study showed significantly better target volume coverage & dose homogeneity with 3DCRT which may translate into better local control & survival but longer follow up is required to validate it.